Filmowa półka sezonu 2011/2012 - Agnieszka Tambor (Postscriptum Polonistyczne)
The article presents a summary of film events of the season 2011/2012. Films that can be found here are: Uwikłanie [Entanglement] directed by Jacek Bromski, Bitwa warszawska 1920 [Battle of Warsaw 1920] – the first Polish movie filmed in 3D, directed by Jerzy Hoffman, Ewa directed by Adam Sikora and Ingmar Villqist, Baby są jakieś inne – a long expected film by Marek Koterski, director of Dzień świra [The Day of the Wacko], Listy do M. [Letters to Santa] by Mitja Okorn, Wymyk by Greg Zgliński, Habemus Papam – an Italian film featuring Jerzy Stuhr directed by Nanni Moretti, Los numeros by Ryszard Zatorski, W ciemności [In Darkness] – Polish film directed by Agnieszka Holland nominated to the Oscar Academy Avard, Trzy minuty 21:37 directed by Maciej Ślesicki. The author endevours to comment on the most famous films of the last year and the beginning of this year, viewing them through the eyes of a foreigner who may be interested in Polish cinema and Polish culture.